Social justice and the urban obesity crisis : implications for social work - Delgado, Melvin (Columbia University Press, 2013)
"Urban America is in the midst of an obesity crisis caused by more than just biology and diet. A number of economic, cultural, and contextual factors are causing this epidemic, which can create chronic health conditions for those least able to manage them. Despite scholars' best efforts to tackle the issue, the problem persists, largely because its social and economic drivers are so subtle and systemic. By considering urban obesity through a social justice lens, this book is the first to help social workers and others develop targeted interventions for truly effective outcomes. Melvin Delgado focuses on urban obesity in populations of color -- among the hardest hit in the United States -- and dissects the issue from individual, family, group, community, and policy perspectives. After an overview surveying the history of urban obesity in communities of color, anti-obesity policies and programs, and the role of social work in addressing this threat, Delgado moves through the social, ecological, environmental, and spatial aggravators of urban obesity, such as the food industry's nefarious advertising strategies, which promote unhealthy choices and behaviors; the failure of local markets to provide good food options; the lack of safe spaces in which to exercise; and the paucity of heath education. He analyzes recent, national statistics in terms of obesity among various groups; explores the connection between foodstamps and obesity; and reveals the financial and social consequences of this issue for society as a whole. Delgado concludes with recommendations for effective health promotion programs, such as youth-focused interventions, community gardens, and community-based food initiatives, and a unique consideration of urban obesity in relation to acts of genocide and the integrity of national defense."--The publisher.